Evaluating Project-Based Learning as a Catalyst for Media Literacy Development in Junior High School Students - Tini, Tini; Ismail, Ismail (Maspul Journal of English Studies, 2024)
The rapid proliferation of digital media underscores the need for enhanced media literacy, particularly among junior high school students who are increasingly exposed to vast, unverified information sources. This study investigates the effectiveness of Project-Based Learning (PBL) as a catalyst for media literacy development, focusing on students at SMPN 7 Anggeraja, Enrekang Regency, South Sulawesi. The objective was to determine whether PBL could improve students’ abilities in accessing, analyzing, and creating media content, while also fostering engagement and collaborative skills. Using a mixed-methods design, this study combined quantitative pre- and post-tests with qualitative interviews and focus groups to capture both measurable outcomes and nuanced insights. Sixty students participated in a six-week PBL intervention, engaging in tasks that required critical evaluation of media sources, identification of media bias, and creation of media content. Pre- and post-intervention assessments revealed statistically significant improvements across all media literacy dimensions, with notable advancements in students’ analytical and creative abilities. Qualitative findings further highlighted increased engagement, motivation, and collaborative skills, as students actively participated in hands-on, group-based projects. These findings underscore PBL’s effectiveness in cultivating critical media literacy competencies and suggest its broader applicability as an educational strategy for fostering digital citizenship skills. By integrating PBL into media literacy curricula, educators can bridge existing instructional gaps, preparing students for responsible media engagement in a complex digital world. This study contributes to the growing body of literature supporting experiential learning models in media literacy education, with recommendations for further research on PBL’s long-term impact and adaptability across diverse educational contexts.